Prevention and Annulment of Marriage in the Perspective of Islamic Law in Indonesia - Muti'ah Nuha Mumtazah; Bagas Eka Syahputra; Khoridatul Bahiyah; Muhammad Zufar Al Faruqi; Novita Fitriani; Kholis Firmansyah (BAYAN: Jurnal Studi Islam dan Humaniora, 2026)
This study demonstrates that the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) has established an integrated system of marriage validity and legal protection through the provisions of Articles 60–97. The validity of marriage is ensured through the mechanisms of marriage prevention and marriage annulment, which function as legal instruments to guarantee that every marriage is conducted in accordance with Islamic principles and applicable legal provisions. Marriage prevention serves as a form of preventive legal protection aimed at avoiding marriages that contain legal defects, while marriage annulment functions as a form of repressive legal protection against marriages that are proven not to fulfill the required conditions and pillars of marriage. In addition to safeguarding the validity of marriage, the Compilation of Islamic Law also provides legal protection for the continuity of family life through the regulation of the rights and obligations of spouses as well as marital property. These regulations reflect the principles of justice, balance, and public welfare (maslahah), which constitute the primary objectives of Islamic family law. Legal certainty regarding the status of husband and wife, as well as the classification of jointly acquired property and individual property, provides protection for the rights of the parties involved while minimizing the potential for disputes within family life. Based on the findings of this study, it can be understood that the provisions of Articles 60–97 of the KHI function not only as legal norms governing family relationships but also as instruments of legal protection that support the realization of families characterized by harmony, justice, and legal certainty. Therefore, efforts to enhance public understanding and effective implementation of these provisions should continue to be promoted among both society and legal practitioners so that the objectives of Islamic family law may be achieved effectively.